Webquest para mejorar la comprensión lectora en la asignatura de Lengua y Literatura en estudiantes de octavo año EGB - Gomez Reyes, Carmen Esther; Tapia Alvarado, Andrea Paola (Machala : Universidad Técnica de Machala, 2025)
This research analyzes the impact of implementing a gamified Webquest on strengthening reading comprehension in eighth-grade students of General Basic Education. The study addresses the problem of low interest and difficulties in text comprehension, a situation observed through traditional teaching methods that do not succeed in motivating or actively involving students. The proposal is based on the design and integration of a Webquest structured around authentic tasks, interactive digital resources, and typical gamification dynamics such as challenges, rewards, levels, and collaborative work. This approach seeks to transform the teaching-learning process, making the development of reading comprehension more attractive, participatory, and meaningful. Methodologically, the research applied a mixed approach (quantitative and qualitative) and a quasi-experimental design with pre-test and post-test. The sample consisted of eighth-grade students from the Unidad Educativa Ciudad de Machala. Surveys and reading comprehension tests were used to evaluate the effectiveness of the Webquest before and after the intervention. The research concludes that the inclusion of innovative technological strategies is essential to improve reading skills, motivate autonomous learning, and prepare students for the educational challenges of the 21st century, recommending their systematic integration into the school curriculum.
Esta investigación analiza el impacto de la implementación de una Webquest gamificada en el fortalecimiento de la comprensión lectora en estudiantes de octavo año de Educación General Básica el estudio responde a la problemática de bajo interés y dificultades en la comprensión de textos, situación observada a través de métodos tradicionales de enseñanza que no logran motivar ni involucrar activamente a los estudiantes. La propuesta parte del diseño e integración de una Webquest estructurada en torno a tareas auténticas, recursos digitales interactivos y dinámicas propias de la gamificación, como retos, recompensas, niveles y trabajo colaborativo, este enfoque busca transformar el proceso de enseñanza-aprendizaje, haciendo el desarrollo de la comprensión lectora más atractivo, participativo y significativo. Metodológicamente, la investigación aplicó un enfoque mixto (cuantitativo y cualitativo) y un diseño cuasi experimental con pretest y postest la muestra estuvo conformada por estudiantes del octavo año de la Unidad Educativa Ciudad de Machala. Se utilizaron encuestas y pruebas de comprensión lectora para evaluar la efectividad de la Webquest antes y después de la intervención. La investigación concluye que la inclusión de estrategias tecnológicas innovadoras resulta fundamental para mejorar competencias lectoras, motivar el aprendizaje autónomo y preparar a los estudiantes para los retos educativos del siglo XXI, recomendando su integración sistemática en el currículo escolar.
Keywords: COMPRENSIÓN LECTORA; WEBQUEST; GAMIFICACIÓN; ESTRATEGIAS DIDÁCTICAS